ARDebug: An Augmented Reality Tool for Analysing and Debugging Swarm Robotic Systems - Millard, Alan G.; Redpath, Richard; Jewers, Alistair M.; Arndt, Charlotte; Joyce, Russell; Hilder, James A.; McDaid, Liam J.; Halliday, David M. (Frontiers in Robotics and AI, 2018)
Despite growing interest in collective robotics over the past few years, analysing and debugging the behaviour of swarm robotic systems remains a challenge due to the lack of appropriate tools. We present a solution to this problem—ARDebug: an open-source, cross-platform, and modular tool that allows the user to visualise the internal state of a robot swarm using graphical augmented reality techniques. In this paper we describe the key features of the software, the hardware required to support it, its implementation, and usage examples. ARDebug is specifically designed with adoption by other institutions in mind, and aims to provide an extensible tool that other researchers can easily integrate with their own experimental infrastructure.